2020
DOI: 10.1111/1468-5973.12329
|View full text |Cite
|
Sign up to set email alerts
|

“It helped us, and it hurt us” The role of social media in shaping agency and action among youth in post‐disaster Nepal

Abstract: This case study explores the communication platforms that youth in Nepal used to respond to the Gorkha earthquake that struck this country on 25 April 2015, and it delves into the role that social media played in shaping the relief efforts initialled and led by youth in Nepal. The data were collected through ethnographic fieldwork and 50 in‐depth interviews conducted in Nepal during the summers of 2015 and 2016 with Nepali youth directly involved in the relief efforts during the immediate aftermath. Findings s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…These results also show a clear likeness to the theory of Ukkusuri et al [47] regarding the approach of the Canary Islands authorities via Twitter to the management of emergencies derived from a natural disaster for service information. According to Dahal [41], social media should be taken as a tool in national crises due to natural disasters.…”
Section: Discussion: Open Innovation Risk Management and Communication Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…These results also show a clear likeness to the theory of Ukkusuri et al [47] regarding the approach of the Canary Islands authorities via Twitter to the management of emergencies derived from a natural disaster for service information. According to Dahal [41], social media should be taken as a tool in national crises due to natural disasters.…”
Section: Discussion: Open Innovation Risk Management and Communication Planningmentioning
confidence: 99%
“…They provide platforms for the rapid detection of natural disasters [33] and quick identification of the problem [36], which serve to properly manage help resources [34]. However, understanding the dynamics of social media with respect to the audience and the use of the information is a challenge that researchers are addressing from the aspects of big data and computer science [26,[37][38][39][40][41].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Social media serve as an important platform where people generate, consume and disseminate informational and emotional content in daily life ( Qu et al, 2009 ), thus becoming a potential attention space for help-seekers to voice for help during public crises ( Alshaabi et al, 2021 ; Andersson & Sundin, 2021 ; Luo et al, 2020 ). Evidence from disaster studies has shown that people voice for help during disasters ( Chu et al, 2021 ; Dahal et al, 2021 ). Several kinds of entities including communities, governments, individuals, organizations, and media outlets are active in the communication on social media during disasters ( Houston et al, 2015 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yonten and fellow participants, through the use of social media platforms such as Facebook, WhatsApp, and Viber, and video calling applications such as Skype, used communication technology to create resources for individuals to gain access for independent rebuilding initiatives or to facilitate larger public participation during events organized through technological mediums. Similarly, from working with 50 youth participants during the earthquake, Dahal et al (2021) explore how through social media, young people in the capacity of youth responders, were able to mobilize crowdsourcing coordination and organizing abilities that supported both community resiliency and their agency as young people to participate in change-making during times of crises. Dahal et al (2021) further prioritize young people's agency through active roles as youth responders by vividly outlining that during the earthquake:…”
Section: The 2015 Earthquake: Young People Assisting With Communication Effortsmentioning
confidence: 99%
“…Similarly, from working with 50 youth participants during the earthquake, Dahal et al (2021) explore how through social media, young people in the capacity of youth responders, were able to mobilize crowdsourcing coordination and organizing abilities that supported both community resiliency and their agency as young people to participate in change-making during times of crises. Dahal et al (2021) further prioritize young people's agency through active roles as youth responders by vividly outlining that during the earthquake:…”
Section: The 2015 Earthquake: Young People Assisting With Communication Effortsmentioning
confidence: 99%